Magnetic Hysteresis Compensation Control of a Magnetorheological Damper - Li, Zhaochun; Gong, Yao; Li, Sihao; Wang, Wanjun (Frontiers in Materials, 2019)
The hysteresis nonlinearity of a magnetorheological (MR) fluid damper is one of the main reasons to restrict it to be widely used in shock buffering fields. This research aims to reduce or eliminate the effect of the magnetic hysteresis of the MR damper. A magnetic hysteresis compensation control method is proposed and verified in this paper. Jiles-Atherton (J-A) model is employed to descript the hysteresis nonlinearity between the adjustable damping force and the actual magnetic induction intensity in the effective damping channel of the MR fluid damper. The simulation of the magnetic compensation control system is performed to evaluate the effectiveness of the proposed method and the employed model. In order to obtain the actual magnetic induction intensity, a MR fluid damper embedded in a Hall sensor is designed and manufactured. The experimental study is carried out to verify the proposed PID control of hysteresis compensation method. Both the simulation results and the experimental results show the MR fluid damper employed proposed hysteresis compensation method with PID control can almost completely eliminate the effect of hysteresis under both low frequency and high frequency input. Furthermore, the experimental results indicate the hysteresis control system of MR fluid damper is of good dynamic performance which make it suitable for the shock buffering system. At last, a simulation model of the MR-damper-based impact buffer system with hysteresis compensation control is established to verify the buffer effect of the system. The output damping force of the MR impact buffer system indicates the buffer performance has been improved by employing the magnetic hysteresis compensation control method.